One-pot synthesis of hierarchical magnetic porous γ-Fe2O3@NiFe2O4 composite with solid-phase morphology changes promoted by adsorption of anionic azo-dye. (February 2020) - Borhan, Adrian Iulian; Gherca, Daniel; Cojocaru, Ştefana; Lupu, Nicoleta; Roman, Tiberiu; Zaharia, Marius; Palamaru, Mircea Nicolae; Iordan, Alexandra Raluca
Graphical abstract: Hierarchical magnetic porous γ-Fe2 O3 @NiFe2 O4 composite was synthesized by sol–gel method. The synthesized composite shows high adsorption capacity for organic anionic dye and could be easily magnetic separated from solutions. Moreover, the adsorption process induced a solid-phase morphology changes from porous-like to fibrous-like structure. Highlights: Preparation of iron oxides-based magnetic porous composite. Investigation of physico-chemical properties of prepared composite. High adsorption capacity of azo dye up to 1.66 g/g according to Langmuir isotherm. Extremely large surface area of 220.53 m 2 g −1 confers special surface properties. Porous γ-Fe2 O3 @NiFe2 O4 as an alternative integrated adsorbent photocatalyst. Abstract: Hierarchical magnetic porous γ-Fe2 O3 @NiFe2 O4 composite was synthesized in air by sol-gel auto-combustion method. Through nitrogen physisorption analysis was found a very large surface area of 220 m 2 /g. Due to the strong molecular host-guest interaction, complemented by the noticeable magnetic properties (Ms = 25 emu/g and Hc = 137 Oe), γ-Fe2 O3 @NiFe2 O4 shows outstanding adsorption performance over anionic dyes, including but not limited to methyl orange. The adsorption process is spontaneous and the pseudo-second-order kinetic model and the Langmuir isotherm model well described the adsorption process. Unquestionably, the excellent adsorption capacity of MO azo dye of 1.66 g/g, according to Langmuir isotherm, promotes morphology changes from porous-like material to fibrous-like structure. The inherent features of morphology changes enhance the photocatalytic activity of the composite by increasing the surface exposure to the visible light. Compared with previously published data, the adsorption capacity of γ-Fe2 O3 @NiFe2 O4 ranks at the top.